Multimodal single-cell analysis of nonrandom heteroplasmy distribution in human retinal mitochondrial disease - Nathaniel K. Mullin; Andrew P. Voigt; Miles J. Flamme-Wiese; Xiuying Liu; Megan J. Riker; Katayoun Varzavand; Edwin M. Stone; Budd A. Tucker; Robert F. Mullins (JCI Insight, 2023)
Variants within the high copy number mitochondrial genome (mtDNA) can disrupt organelle function and lead to severe multisystem disease. The wide range of manifestations observed in patients with mitochondrial disease results from varying fractions of abnormal mtDNA molecules in different cells and tissues, a phenomenon termed heteroplasmy. However, the landscape of heteroplasmy across cell types within tissues and its influence on phenotype expression in affected patients remains largely unexplored. Here, we identify nonrandom distribution of a pathogenic mtDNA variant across a complex tissue using single-cell RNA-Seq, mitochondrial single-cell ATAC sequencing, and multimodal single-cell sequencing. We profiled the transcriptome, chromatin accessibility state, and heteroplasmy in cells from the eyes of a patient with mitochondrial encephalopathy, lactic acidosis, and stroke-like episodes (MELAS) and from healthy control donors. Utilizing the retina as a model for complex multilineage tissues, we found that the proportion of the pathogenic m.3243A>G allele was neither evenly nor randomly distributed across diverse cell types. All neuroectoderm-derived neural cells exhibited a high percentage of the mutant variant. However, a subset of mesoderm-derived lineage, namely the vasculature of the choroid, was near homoplasmic for the WT allele. Gene expression and chromatin accessibility profiles of cell types with high and low proportions of m.3243A>G implicate mTOR signaling in the cellular response to heteroplasmy. We further found by multimodal single-cell sequencing of retinal pigment epithelial cells that a high proportion of the pathogenic mtDNA variant was associated with transcriptionally and morphologically abnormal cells. Together, these findings show the nonrandom nature of mitochondrial variant partitioning in human mitochondrial disease and underscore its implications for mitochondrial disease pathogenesis and treatment.